Preliminary Criteria for Global Flares in Childhood-Onset Systemic Lupus Erythematosus - Brunner, Hermine I.; Mina, Rina; Pilkington, Clarissa; Beresford, Michael W.; Reiff, Andreas; Levy, Deborah M.; Tucker, Lori B.; Eberhard, B. Anne; Ravelli, Angelo; Schanberg, Laura E.; Saad-Magalhaes, Claudia [UNESP]; Higgins, Gloria C.; et al. (Wiley-Blackwell, 2011)
Objective. To develop widely acceptable preliminary criteria of global flare for childhood-onset systemic lupus erythematosus (cSLE).Methods. Pediatric rheumatologists (n = 138) rated a total of 358 unique patient profiles with information about the cSLE flare descriptors from 2 consecutive visits: patient global assessment of well-being, physician global assessment of disease activity (MD-global), health-related quality of life, anti-double-stranded DNA antibodies, disease activity index scores, protein: creatinine (P:C) ratio, complement levels, and erythrocyte sedimentation rate (ESR). Based on 2,996 rater responses about the course of cSLE (baseline versus followup), the accuracy (sensitivity, specificity, and area under the receiver operating characteristic curve) of candidate flare criteria was assessed. An international consensus conference was held to rank these candidate flare criteria as per the American College of Rheumatology recommendations for the development and validation of criteria sets.Results. The highest-ranked candidate criteria considered absolute changes (Delta) of the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) or British Isles Lupus Assessment Group (BILAG), MD-global, P:C ratio, and ESR; flare scores can be calculated (0.5 x Delta SLEDAI + 0.45 x Delta P:C ratio + 0.5 x Delta MD-global + 0.02 x Delta ESR), where values of >= 1.04 are reflective of a flare. Similarly, BILAG-based flare scores (0.4 x Delta BILAG + Delta 0.65 x Delta P:C ratio + 0.5 + Delta MD-global + 0.02 x Delta ESR) of >= 1.15 were diagnostic of a flare. Flare scores increased with flare severity.Conclusion. Consensus has been reached on preliminary criteria for global flares in cSLE. Further validation studies are needed to confirm the usefulness of the cSLE flare criteria in research and for clinical care.